The eclipse of private equity - Cheffins, B; Armour, J (Widener University School of Law, 2008)
Private equity, characterized by firms operating as privately held partnerships organizing the acquisition and “taking private” of public companies, has recently dominated the business news due to deals unprecedented in number and size. If this buyout boom continues unabated, the 1989 prediction by economist Michael Jensen of The Eclipse of the Public Corporation could be proved accurate. This article argues matters will work out much differently, with the current version of private equity being eclipsed. One possibility is that a set of market and legal conditions highly congenial to “public-to-private” transactions could be disrupted. A “credit crunch” commencing in the summer of 2007 stands out as the most immediate threat. The article draws on history to put matters into context, discussing how the spectacular rise of conglomerates in the 1960s was reversed in subsequent decades and how the 1980s buyout boom led by leveraged buyout associations-the private equity firms of the day collapsed. If legal and market conditions remain favorable for private equity, its eclipse is likely to occur in a different way. Privacy has been a hallmark of private equity, with industry leaders operating as secretive partnerships that negotiate buyouts behind closed doors and restructure portfolio companies outside the public gaze. However, the private equity boom created momentum among market leaders to carry out public offerings and diversify their operations. If this trend proves sustainable, then even if the taking private of publicly quoted companies remains a mainstream pursuit, the exercise will be carried out in the main by broadly based financial groups under the umbrella of public markets.